KONSEP KEPEMIMPINAN PENDIDIKAN DALAM MENGEMBANGKAN PRINSIP PEMBERDAYAAN MASYARAKAT - Marjuni, H. Andi (Inspiratif Pendidikan, 2022)
Leadership is the process of inspiring others to work hard to achieve important work. Leadership builds commitment and enthusiasm for people to implement their talents to help achieve plans, oversight so as to make sure everything goes well. In its activities, the leader has the power to mobilize and influence his subordinates with respect to the tasks that must be carried out. At the stage of assigning tasks, the leader must provide clear direction and guidance, so that subordinates can carry out their duties easily and the results achieved are in accordance with the goals that have been set. Conceptually, the term empowerment has the basic word "daya" which means ability, strength, effort, ability to do business. Empowerment in education can be interpreted as a process of making human resources capable or strong in carrying out a business in a particular field in the field of education. , including reducing the effects of personal and social barriers to action